Inhibitory control in teleost fish: a methodological and conceptual review - Tyrone Lucon-Xiccato (Animal Cognition)
Abstract Inhibitory control (IC) plays a central role in behaviour control allowing an individual to resist external lures and internal predispositions. While IC has been consistently investigated in humans, other mammals, and birds, research has only recently begun to explore IC in other vertebrates. This review examines current literature on teleost fish, focusing on both methodological and conceptual aspects. I describe the main paradigms adopted to study IC in fish, identifying well-established tasks that fit various research applications and highlighting their advantages and limitations. In the conceptual analysis, I identify two well-developed lines of research with fish examining IC. The first line focuses on a comparative approach aimed to describe IC at the level of species and to understand the evolution of interspecific differences in relation to ecological specialisation, brain size, and factors affecting cognitive performance. Findings suggest several similarities between fish and previously studied vertebrates. The second line of research focuses on intraspecific variability of IC. Available results indicate substantial variation in fish IC related to sex, personality, genetic, age, and phenotypic plasticity, aligning with what is observed with other vertebrates. Overall, this review suggests that although data on teleosts are still scarce compared to mammals, the contribution of this group to IC research is already substantial and can further increase in various disciplines including comparative psychology, cognitive ecology, and neurosciences, and even in applied fields such as psychiatry research.